'[It] isn't designed to be assessed how we assess': rethinking assessment for qualification in the context of the implementation of the Curriculum for Wales. Issue 2 (25th February 2020) - Titley, Elizabeth; Davies, Andrew James; Atherton, Stephen
Abstract : This paper reports teacher and learner perspectives on how assessment and reform influences pedagogical practices and behaviours. The research was conducted in a context of policy reform, at a time when Wales' revised General Certificate of Secondary Education (GCSE) specifications had been implemented, and learners were preparing for their assessments; but, also during the period of debate on the development of Wales' new curriculum, which has taken a distinct and contrasting position on assessment to the assumptions underlying the reform of Welsh GCSEs implemented from 2015. These data, therefore, offer unique insights into the affordances and limitations of two sharply contrasting systems at a time of considerable change, offering reflections on the current curriculum and its attendant assessment practices, and also a prospective analysis of how the principles embedded in the new curriculum could challenge these existing assumptions and conventions. Findings suggest that teachers and learners currently inhabit an assessment‐driven system, which encourages performative practices in pedagogy and is governed by external accountability; and that these practices are at odds with the principles of assessment articulated in Successful Futures . Consequently, teachers in this study expressed uncertainty about how assessment for certification purposes at GCSE could be compatible with the principles of the Curriculum for Wales.